Digital Accounting In Pursuit Of Environmental Sustainability - Ahmed Fadhil Saleh; Ghalib J. Aswad; Ahmed Mohammed Khalaf (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The research paper discusses the findings of the literature of previous studies related to accounting digitization to achieve environmental sustainability for the period from 2013 to 2023. The conclusions of the research literature show how the concept of modernity and the importance of digitization in accounting has evolved over the past few years in shedding light on different destinations and topics in the field of decision-making and environmental protection. The findings appears that researchers pointed to the urgent need to link research disciplines that would lead to increased interest in clean energy by involving experts in leading the digital transformation of accounting to legitimize the work of accountants. This research paper also referred to the results of the literature of studies regarding the interaction between various fields, especially sustainable accounting and accounting information systems, where the role of digital accounting in achieving sustainability, which is an integral part of a network of human and non-human actors that reflects economic activities on the environment. New research must also take into account that technology alone cannot solve environmental issues in isolation from the interactive role with humans who jointly seek solutions. Therefore, automating the work of accountants interested in corporate social responsibility issues through digital accounting can be one of the main pillars of that interaction in order to improve decision-making to protect the environment.